How do you factor x^5+5x^4+6x^3?
2 Answers
Explanation:
First note that all of the terms are divisible by
x^5+5x^4+6x^3 = x^3(x^2+5x+6)
To factor the remaining quadratic, we want to find two numbers whose sum is
(x+p)(x+q) = x^2+(p+q)x+pqx
The numbers
x^2+5x+6 = (x+2)(x+3)
Putting it all together:
x^5+5x^4+6x^3 = x^3(x+2)(x+3)
Explanation:
Factorization is accomplished by taking a common factor ,completing the square, applying the polynomial identities ,or using the quadratic formula .
The expression
For the expression
For the whole expression
Therefore,